Remodelling of femoral head deformity after hip reconstructive surgery in patients with cerebral palsy - Min, J. J.; Kwon, S. S.; Sung, K. H.; Lee, K. M.; Chung, C. Y.; Park, M. S. (Bone and Joint Journal, 2021)
Aims Hip displacement, common in patients with cerebral palsy (CP), causes pain and hinders adequate care. Hip reconstructive surgery (HRS) is performed to treat hip displacement; however, only a few studies have quantitatively assessed femoral head sphericity after HRS. The aim of this study was to quantitatively assess improvement in hip sphericity after HRS in patients with CP. Methods We retrospectively analyzed hip radiographs of patients who had undergone HRS because of CP-associated hip displacement. The pre- and postoperative migration percentage (MP), femoral neck-shaft angle (NSA), and sphericity, as determined by the Mose hip ratio (MHR), age at surgery, Gross Motor Function Classification System level, surgical history including Dega pelvic osteotomy, and triradiate cartilage status were studied. Regression analyses using linear mixed model were performed to identify factors affecting hip sphericity improvement. Results A total of 108 patients were enrolled. The mean preoperative MP was 58.3% (SD 31.7%), which improved to 9.1% (SD 15.6%) at the last follow-up. NSA and MHR improved from 156.5° (SD 11.5°) and 82.3% (SD 8.6%) to 126.0° (SD 18.5°) and 89.1% (SD 9.0%), respectively. Factors affecting the postoperative MHR were preoperative MP (p = 0.005), immediate postoperative MP (p = 0.032), and history of Dega osteotomy (p = 0.046). Conclusion We found that hip sphericity improves with HRS. Preoperative MP, reduction quality, and acetabular coverage influence femoral head remodelling. We recommend that surgeons should consider intervention early before hip displacement progresses and that during HRS, definite reduction and coverage of the femoral head should be obtained.
Keywords: Bone Remodeling; Cerebral Palsy; Child; Female; Femur Head; Hip Dislocation; Humans; Male; Osteotomy; Reconstructive Surgical Procedures; Retrospective Studies